Development and Optimisation of a Robot Arm System for Additive Manufacturing Applications - L. Stamorean; A. Feier; A. C. Firu (Annals of "Dunarea de Jos" University of Galati, Fascicle XII, Welding Equipment and Technology, 2023)
The paper presents the development of a new platform that represents a robotic arm system, useful and appropriate for the Additive Manufacturing applications. The main objective of this work was to explore the feasibility of integrating the off-the-shelf (COTS) Additive Manufacturing technologies and the six-degree-of-freedom industrial robotic arm, achieving a 3D Additive Manufacturing system which is able to perform six-degree fused deposition printing. The authors investigated the materials suitable to be used and performed more experiments with the aim to find the right configuration of the printing system. Finally, the technical issues reported during the experimental programme have been solved, the system being prepared to carry out workpieces with more complex shapes and more types of polymers.